Determinants of export performance of SMEs in the Kyrgyz Republic - Kamalbek Karymshakov (Asian Development Bank Institute (ADBI), 2020)
Increased participation in global value chains is firmly related to the engagement of local producers in international markets through increasing sales in these markets. This study aims to examine factors affecting export performance of SMEs in the Kyrgyz Republic. Empirical estimations based on the Enterprise Survey data set reveal that correspondence with quality requirements, increasing participation of foreign capital in ownership of firms, availability of financial resources, and labor productivity are important determinants of exporting activities of SMEs. Along with this, firms in industries with a low technology level demonstrate relatively higher export activities. However, it can also be argued that SMEs do not have enough capability to adopt medium and high technology in their production process, which may lead to concern over the long-term sustainability of their competitiveness in international markets. These findings underline that government policy towards enhancing labor productivity, foreign capital participation associated with the higher availability of financial resources, and knowledge-supporting programs are important for the export of SMEs in the Kyrgyz Republic.
Keywords: F14; L25; L26; 330; SME; export; internationalization